PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH, SUPERVISI DAN KOMPETENSI GURU TERHADAP KINERJA GURU SD STRADA CABANG JAKUTTIM - Leonardus Jelanu; Widi Dewi Ruspitasari; Murtianingsih Murtianingsih (Smart Education, 2024)
This study aims to identify and analyze: 1) The influence of the headmaster's leadership style on the performance of elementary school teachers at SD Strada Branch North-East Jakarta. 2) The influence of supervision on the performance of elementary school teachers at SD Strada Branch North-East Jakarta. 3) The influence of teacher competence on the performance of elementary school teachers at SD Strada Branch North-East Jakarta. 4) The influence of the principalâ€™s leadership style, teacher competence, and supervision on the performance of elementary school teachers at SD Strada Branch North-East Jakarta.The sampling method used is purposive sampling. Respondents in this study are all elementary school teachers at SD Strada Branch North-East Jakarta. Data collection is conducted through the distribution of questionnaires via Google Form. The research results indicate that the headmaster's leadership style variable does not significantly influence the performance of elementary school teachers at SD Strada Branch North-East Jakarta. Similarly, the supervision variable also does not significantly influence their performance. However, the teacher competence variable has a positive and significant influence on their performance. The variables of headmaster's leadership style, supervision, and teacher competence together significantly influence the performance of elementary school teachers at SD Strada Branch North-East Jakarta.Â Keyword: Headmaster's Leadership Style, Supervision, Teacher Competence, Teacher Performance.